The Situation Room: A Step by Step Procedure toward Pandemic Influenza Preparedness - Miguel Angel Castro-Jiménez; Lina María Vera-Cala; Gloria Janneth Rey-Benito (Journal of Infection in Developing Countries)
In the context of the public health surveillance, the situation room might be playing an interesting role as a strategy for early alert and follow-up of a specific public health event and its determinants. The implementation and proper functioning of an influenza situation room monitoring seasonal and pandemic influenza or any other public health event could help to mitigate the impact of the next pandemic on public health in any country regardless of its level of economic development. This paper is aimed to suggest some basic steps for implementing an Influenza Situation Room as a strategy of prevention of diseases with potential to cause human pandemics and its mitigation if it has already occurred.